Implementation of Positive Language to Promote Effective Language Teaching Classrooms for State Junior High School - Rosyada, Amrina; Widyastuti, Ana; Ramadhianti, Agustina (Lingua Cultura, 2018)
The research aimed to determine the influence of positive language to promote the effective language teaching classrooms in state junior high school. The effective language teaching classroom was measured quantitatively by applying a correlational research design. The method conducted several steps as procedures of investigation in analyzing the data, namely: (1) data collection,(2) data analysis, and (3) data interpretation. Engaged by 142 students of eighth-grade and four language teachers, findings have shown that there is a positive correlation between positive language and effective language teaching classrooms. The results are hoped to be as teachers’ and students’ guidance in implementing positive language to building their effective language teaching classrooms, gaining their confidence and ability to learn and use knowledge and skills to interact and fully participate in education.